Characteristics of pre-service mathematics teacher when solving convergent sequence problems - Nursupiamin; Rochaminah, Sutji (Universitas Islam Negeri (UIN) Mataram, 2024)
[English]: Convergent sequences pose a challenge for students to comprehend in real analysis courses. Problem-solving based learning can serve as an alternative approach for imparting the understanding of convergent sequences. The objective of this research is to provide a description of the activities undertaken by students when solving problems related to convergent sequences, focusing on specific characteristics of their problem-solving approaches. This study used a qualitative methodology, namely a case study design, with a sample size of 14 participants who were recruited using purposive sampling. The collection of data was conducted via tests and interviews. The findings of this study indicate that the participants can be classified into dominant representation groups and non-dominant representation groups. The subjects who are verbally dominant tend to express ideas using precise language, possess the ability to elaborate on concepts, and demonstrate logical reasoning and argumentation skills. The subjects who are visually dominant tend to analyze or convert visual representations throughout the process of problem-solving. Meanwhile, those who are symbolically dominant tend to approach problem-solving by breaking down the difficulties into multiple solution phases that are conceptually organized. The subjects who are not dominant in a certain type of representation show flexibility in understanding the problem by using a variety of representations that are appropriate for their situation and level of knowledge. The results of this study can serve as a guide for constructing educational approaches, taking into account the characteristics of students when solving problems related to convergent sequences. [Bahasa]: Barisan konvergen merupakan salah satu konsep yang sulit dipahami peserta didik pada matakuliah analisis real. Pembelajaran berbasis pemecahan masalah dapat menjadi alternatif untuk menanamkan konsep barisan konvergen. Penelitian ini bertujuan untuk mendeskripsikan aktivitas peserta didik dalam memecahkan masalah barisan konvergen berdasarkan representasi matematis yang mereka kembangkan. Kajian ini menggunakan pendekatan kualitatif dengan jenis studi kasus yang melibatkan 14 responden yang dipilih secara purposive sampling. Data dikumpulkan menggunakan instrumen tes dan pedoman wawancara. Hasil penelitian ini menunjukkan bahwa responden dapat dikategorikan menjadi kelompok representasi dominan dan kelompok representasi tidak dominan. Responden yang dominan verbal cenderung menyampaikan ide melalui kata-kata yang jelas, mampu merincikan konsep serta menyusunnya dengan argumen dan pemikiran yang logis. Responden yang dominan visual cenderung menginterpretasikan atau menerjemahkan tampilan visual dalam membangun tahapan pemecahan masalah. Adapun responden dominan simbolik cenderung memecahkan masalah dengan menguraikannya menjadi beberapa langkah penyelesaian yang terstruktur secara konseptual. Karakteristik responden yang tidak dominan pada satu tipe representasi menunjukkan fleksibilitas mahasiswa dalam memahami masalah dengan menggunakan beragam representasi yang disesuaikan dengan kondisi dan pengetahuan yang dimiliki. Temuan penelitian ini dapat menjadi acuan untuk merancang skenario pembelajaran berdasarkan karakteristik individu dalam pemecahan masalah barisan konvergen.